Memórias do Campus Tabatinga/IFAM: uma década de presença na região do Alto Solimões - Villar, Denise Targino (2023)
This research had as object of study the Tabatinga/IFAM Campus, whose objective was to describe the history of the Tabatinga/IFAM Campus through documentary and bibliographic sources and the memories of teachers of Integrated High School, between the founding period of the Tabatinga Campus in the Triple Amazonian Border region (Brazil-Colombia and Peru) in 2010 and when it completed a decade of existence in the region in 2020, a very specific period of history, which was the year of the Sars-CoV Pandemic -2 that changed so many areas and education was one of them with the implementation of emergency remote education and its technologies. In this way, we sought to understand the concept of integral human formation that is a central element for technical and technological education. To guide the discussion of this conceptual basis, we resorted to Freire (1996), Gadotti (2011), Ciavatta (2010) and Pacheco (2010). In the discussion involving memory and oral history Thompson (2006) and Demartini (2006). To analyze the questionnaire and interview that were applied with the teachers of integrated high school, we resorted to the methodology of Bardin (2006) for content analysis. We hope that the research has demonstrated the importance that the Tabatinga/IFAM Campus assumes in the region in the educational field on the basis of integral human formation. As an educational product of this research, a photographic exhibition was created with ten photographs on fabric. The photographs symbolically represent each year of existence of the institution, besides other elements that add to the exhibition such as a replica of a typical transport of the region, known as Baleeira and a fabric canvas with the image of the Solimões River plus an excerpt of a poem by the writer and indigenous poet Márcia Kambeba. The photographic exhibition had the characteristic of contributing to the institution's publicity among the school community and the general public.